Avaliação do risco soberano dos países da América Latina - 2000 a 2017 - Morelo, Gregory Gilmar (Universidade do Vale do Rio dos Sinos, 2009)
The aim of this study is to verify the relationship between the sovereign risk of Latin American countries and their macroeconomic variables such as public debt, current account balance, gross domestic product and portfolio investment balance, from 2000 to 2017. The countries analyzed were Argentina, Brazil, Chile, Colombia, Mexico and Peru, because they correspond to the largest economies in Latin America. The applied methodology is based on Granger causality tests and the autoregressive vector models, with analysis by the impulse response function and variance decomposition. As main results, significant relationships were found between sovereign risk and gross domestic product in Brazil, Chile, Colombia and Peru, where causality was identified between the variables and negative effects on GDP when sovereign risk shocks were attributed. In addition, there were significant relationships between sovereign risk and public debt for Argentina, Colombia, Mexico and Peru. Argentina, Brazil, Chile, Colombia and Peru also demonstrated significant relationship between sovereign risk and current account balance. Sovereign risk and portfolio investments showed significant results in the Mexican economy. Thus, it was found that variations in sovereign risk are relevant and have significant effects on the economy of countries. This highlights the importance of sovereigns pursuing responsible policies to minimize negative effects associated with the level of risk attributed to them.
Keywords: Risco soberano; Macroeconomia; América Latina; Sovereign risk; Macroeconomics; Latin America; ACCNPQ::Ciências Sociais Aplicadas::Economia